Effectiveness of Project-Based Learning on Improving Creative Thinking Skills: Efektivitas Penerapan Project-Based Learning Terhadap Peningkatan Keterampilan Berpikir Kreatif - Oktaviani, Safira; Safitri, Sani (CV. Media Publikasi Profesional, 2024)
This study aims to explore the effectiveness of Project-Based Learning (PJBL) model in improving students' creative thinking skills as a response to the limitations of traditional learning methods that do not stimulate creativity. Using a quantitative approach through a one-group pretest-posttest experimental design, the study involved nine students who were active in project-based learning. Data were collected through creative thinking skills tests before and after the application of the model, and analysed using descriptive and inferential statistics. The results showed a significant increase in the mean score from 47.3 in the pretest to 85.6 in the posttest, indicating that PjBL is effective in encouraging the development of students' creativity, active participation, and collaboration. This finding has implications for the need to integrate PjBL in the curriculum and strengthen teacher training to systematically improve students' 21st century competencies. The originality of this study lies in emphasising that collaboration in project work is a key factor in strengthening creative thinking, thus expanding the understanding of innovative student-centred learning strategies.